Kedudukan Politik Dalam Membangun Perkembangan Pendidikan Islam - Asy'arie, Bima Fandi; Mun’im, Zainul; Ma’ruf, Rachmad Arif; Susanti, Septiani Selly; Kurniawati, Dhoni (LP2M Universitas Islam Ahmad Dahlan, 2024)
This research aims to (1) determine the political position of those holding power in a country. (2) Know the categories of Islamic education, both formal and informal education. (3) Describe the role of politics in developing Islamic education in Indonesia. This research uses a type of library (library research). Data was obtained through searching “Google Scholar” and “ScienceDirect”, namely books, e-books, scientific journals, proceedings, the internet, and similar publications. The analysis process is carried out by collecting data, reducing and categorizing data, presenting data, and drawing conclusions relevant to the research subject. The results of this research are: First, there are three divisions of power in Indonesia, legislative, namely the power to make laws; executive, namely the power to implement laws; and the judiciary is the power to judge violations of the law. Second, the division of types of Islamic education, including formal education “Madrasah Ibtidaiyah (MI), Madrasah Tsanawiyah (MTs), Madrasah Aliyah (MA), and Islamic Religious Colleges”. Then, non-formal education